Preparation method and application of flexible polymer electrolyte for rapid fluorine ion conduction
Through the electrolytes of flexible polymerization preparation of the legal system, the problem of electrolyte deficiency in the fluorine ion battery is solved, and the fluorine ion battery of high energy density and long cycle life is realized.
Patent Information
- Application Number
- CN202411417626.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-01-21
AI Technical Summary
The existing fluorine ion batteries lack suitable electrolytes, which lead to electrochemical irreversibility at low temperatures, and the solid electrolyte is statically formed under high pressure, with an interface impedance hindering the transmission of ions.
The electrolyte of flexible polymer is prepared by the organic polymer macromolecular and inorganic fluorine salt as the raw material, and the proportion of polymer macromolecules and inorganic fluorine salts is used to increase the ion conductivity.
The flexible polymerization electrolyte of high ion conductivity is achieved, which significantly improves the energy density and cycle life of fluorine ion batteries.
Smart Images

Figure CN119340465A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of fluoride ion electrolytes, and in particular to a preparation method and application of a flexible polymer electrolyte with fast fluoride ion conduction. Background Art
[0002] As a new force in the field of battery technology, fluoride ion batteries are regarded as a strong competitor for the next generation of battery technology due to their high energy density, good safety and high abundance of fluorine in the earth's crust. Compared with traditional lithium-ion batteries, fluoride ion batteries are expected to overcome problems such as limited energy density, tight lithium resource supply and safety risks.
[0003] However, the lack of suitable electrolytes has limited the rapid development of fluoride ion batteries. In early studies, the cycle performance of fluoride ion batteries that can achieve stable charge and discharge at room temperature was limited, and the discovery of new solid electrolytes has brought breakthroughs in this field. For example, in 2011, Anji Reddy, Fichtner and others successfully prepared La using the mechanical spheroidal graphite method. 1-x Ba x F 3-x (0≤x≤0.15) solid electrolyte. They fabricated the first rechargeable fluoride ion battery based on metal / metal fluoride combinations such as BiF3, CuF2, SnF2 and KBiF4 as electrodes, La 0.9 Ba 0.1 F 2.9 At 160℃, the ionic conductivity is about 2.8×10 -4 S cm -1 , and experimentally confirmed the electrode reactions of these electrodes in fluoride ion batteries. [Anji Reddy, M. & Fichtner, M. Batteries based on fluoride shuttle. Journal of Materials Chemistry 21 (2011)] Since then, the research on solid electrolytes for fluoride ion batteries has attracted widespread interest. However, the solid electrolytes currently used, including fluorcerium ore and fluorite phase fluoride, only have sufficiently high ionic conductivity (~10 -4 S cm -1 ), and the electrochemistry is irreversible at low temperatures. In addition, solid electrolytes are usually statically pressed under high pressure, and there is a large interface impedance between the interface and the electrode material, which seriously hinders the transmission of ions. Therefore, it is urgent to develop a new type of fluoride ion electrolyte to achieve high energy density all-solid-state fluoride ion batteries.
[0004] Polymer electrolytes are a new type of electrolyte material with high theoretical energy density. They have potential application value in all-solid-state fluoride ion batteries and have aroused the interest of researchers due to their enhanced safety characteristics and superior capacity. The ion conduction mechanism and improvement strategy of polymer electrolytes have always been a hot research topic in the field of lithium-ion batteries. In a review article, Professor Guo Xin's team from Huazhong University of Science and Technology summarized the research progress of polymer-based solid electrolytes in recent years and deeply analyzed the strategies for improving ionic conductivity and optimizing interface properties [Li Z, Fu J, Zhou X, et al. Ionic conduction in polymer-based solid electrolytes [J]. Advanced Science, 2023, 10 (10): 2201718.]. Academician Chen Jun of Nankai University and others developed a multispectral characterization strategy to unravel the mystery of the ion conduction mechanism by analyzing the polyvinylidene fluoride hexafluoropropylene (PVDF-HFP) model system with excellent electrochemical stability [He X, Ni Y, Hou Y, et al. Insights into the ionic conduction mechanism of Quasi-solid polymer electrolytes through multispectral characterization [J]. Angewandte Chemie, 2021, 133 (42): 22854-22859.]. For fluoride ion batteries, only Luo Kaili's team at Xiangtan University reported the inorganic nanoparticle La 0.95 Ba 0.05 F 2.95 Dispersed in polymer PEO solution.
Liu, L., Yang, L., Liu, M., Wang, X., Li, X., Shao, D., Luo, K., Luo, Z. & Chen, G. A flexible tysonite-type La 0.95 Ba 0.05 F 2.95 @PEO-based composite electrolyte for the application of advanced fluoride ion battery.Journal of Energy Storage 25(2019).
[0005] In view of the above problems, the purpose of the present invention is to provide a method for preparing a flexible polymer electrolyte with fast fluoride ion conduction and its use. In order to achieve the above purpose, the technical solution adopted by the present invention is: using organic polymer macromolecules and inorganic fluoride salts as raw materials, a flexible polymer electrolyte is prepared by a tape casting method. The prepared polymer electrolyte has high ionic conductivity and can achieve high energy density of fluoride ion batteries.
[0006] In a first aspect, the present invention aims to provide a method for preparing a flexible polymer electrolyte with fast fluoride ion conduction, which is prepared by the following steps:
[0007] Step 1: Weigh polymer macromolecules and inorganic fluoride salts as raw materials in a certain molar ratio. First, add a certain mass of polymer macromolecules into a beaker containing a certain volume of organic solvent and stir until completely dissolved. Then add inorganic fluoride salts to the above solution and continue stirring for a certain period of time to obtain a uniform polymer solution.
[0008] Step 2: Inject the polymer solution obtained in step 1 into a customized polytetrafluoroethylene mold, let it stand at room temperature for a period of time, then transfer it to a vacuum oven, and heat it at a set temperature for a period of time until the organic solvent is completely evaporated to obtain a flexible polymer electrolyte.
[0009] The present invention prepares a flexible polymer electrolyte by a tape casting method, which is easy to manipulate and convenient for mass preparation. The ionic conductivity of the polymer electrolyte is regulated by controlling the ratio of polymer macromolecules and inorganic fluoride salts, thereby improving the performance of fluoride ion batteries. Therefore, the polymer electrolyte of the present invention has high flexibility, strong film-forming ability, and high ionic conductivity. When used as a fluoride ion battery electrolyte, it can significantly improve the energy density and cycle life of the fluoride ion battery.
[0010] Preferably, the molar ratio of the polymer macromolecule and the inorganic fluoride salt selected in step 1 is 18:1, 16:1, 12:1, 10:1, 8:1, 5:1, 3:1, 2:1 or 1:1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0011] Preferably, the polymer macromolecule selected in step 1 includes any one of polyvinylidene fluoride, polyacrylonitrile, polyethylene oxide, polymethyl methacrylate, polyethylene imine, polypropylene, carboxymethyl cellulose, alginate, pectinate, carrageenan, or a combination of at least two thereof, preferably polyethylene oxide.
[0012] Preferably, the inorganic fluoride salt selected in step 1 includes any one of sodium fluoride, potassium fluoride, cesium fluoride, and rubidium fluoride, or a combination of at least two thereof, preferably cesium fluoride.
[0013] Preferably, the mass of the polymer macromolecule selected in step 1 is 0.5-1.0 g, which can be 0.5 g, 0.6 g, 0.7 g, 0.8 g, 0.9 g or 1.0 g, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0014] Preferably, the organic solvent selected in step 1 includes any one of methanol, ethanol, acetone, chloroform, ether, acetonitrile, dimethyl sulfoxide, tetrahydrofuran, N,N-dimethylformamide, or a combination of at least two thereof, preferably acetonitrile solvent.
[0015] Preferably, the volume of the organic solvent selected in step 1 is 15-40 ml, which can be 15 ml, 20 ml, 25 ml, 30 ml, 35 ml or 40 ml, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0016] Preferably, the stirring time selected in step one is 12-48h, for example, it can be 12h, 16h, 20h, 24h, 28h, 32h, 36h, 40h, 44h or 48h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0017] Preferably, the standing time selected in step 2 includes 6-24 hours, for example, it can be 6 hours, 12 hours, 18 hours or 24 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0018] Preferably, the heating temperature selected in step 2 includes 60-80°C, for example, 60°C, 65°C, 70°C, 75°C or 80°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0019] Preferably, the heating time selected in step 2 includes 12-24 hours, for example, it can be 12 hours, 14 hours, 16 hours, 18 hours, 20 hours or 24 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0020] As a preferred technical solution of the preparation method described in the first aspect of the present invention, the preparation method comprises:
[0021] Step 1: Weigh polymer macromolecules and inorganic fluoride salts as raw materials at a molar ratio of 18:1-1:1. First, add 0.5-1.0 g of polymer macromolecules into a beaker containing 15-40 ml of organic solvent and stir until completely dissolved. Then add inorganic fluoride salts to the above solution and continue stirring for 12-48 hours to obtain a uniform polymer solution.
[0022] Step 2: Inject the polymer solution obtained in step 1 into a customized polytetrafluoroethylene mold, let it stand at room temperature for 6-24 hours, then transfer it to a vacuum oven, and heat it at 60-80°C for 12-24 hours until the organic solvent is completely evaporated to obtain a flexible polymer electrolyte.
[0023] In a second aspect, the present invention provides a flexible polymer electrolyte, wherein the flexible polymer electrolyte is obtained by the preparation method described in the first aspect.
[0024] Preferably, the flexible polymer electrolyte has the characteristics of high flexibility, strong film-forming ability, low interface resistance with electrodes, and high ionic conductivity.
[0025] In a third aspect, the present invention provides a use of a flexible polymer electrolyte, wherein the flexible polymer electrolyte is obtained by the preparation method described in the first aspect. The flexible polymer electrolyte is assembled with a metal fluoride / carbon composite material positive electrode and a lead foil negative electrode for use in a fluoride ion battery.
[0026] Preferably, the metal fluoride composite material positive electrode is prepared by mixing metal fluoride and mesoporous carbon material by ball milling, and then grinding the metal fluoride / mesoporous carbon: binder PVDF: conductive agent acetylene black in a ratio of 8:1:1, adding NMP solution to prepare a suspension, and coating it on a single-sided carbon-coated aluminum foil to prepare a positive electrode sheet.
[0027] Preferably, the selected metal fluoride includes any one of copper fluoride, cuprous fluoride, ferric fluoride, ferrous fluoride, manganese fluoride, bismuth fluoride, lead fluoride, magnesium fluoride, calcium fluoride, and barium fluoride, or a combination of at least two thereof, preferably copper fluoride.
[0028] Preferably, the method for using the flexible polymer electrolyte is to sequentially place the positive electrode material of the fluoride ion battery, the flexible polymer electrolyte, and the negative electrode material in a CR2032 commercial button battery for assembly testing.
[0029] Preferably, the fluoride ion battery has a high initial specific capacity>500 mAh g -1 , capable of 250 cycles.
[0030] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0031] Compared with the prior art, the present invention has the following advantages:
[0032] 1. The present invention prepares a flexible polymer electrolyte by a tape casting method, which is low in price, easy to control, and convenient for large-scale preparation.
[0033] 2. The flexible polymer electrolyte prepared by the present invention has the characteristics of high flexibility, low interface resistance with the electrode, strong film-forming ability, and high ionic conductivity.
[0034] 3. The present invention improves the ionic conductivity of the polymer electrolyte by controlling the ratio of the polymer salt and the fluoride salt, thereby increasing the specific capacity of the fluoride ion battery to >500 mAh g -1 , loop 250 times. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 Electrochemical impedance spectroscopy of a polymer electrolyte prepared with a molar ratio of polyethylene oxide to cesium fluoride of 3:1 (the inset is a partial enlarged view)
[0036] Figure 2 Arrhenius curves of polymer electrolytes prepared with different molar ratios of polyethylene oxide and cesium fluoride
[0037] Figure 3 Linear sweep voltammetry curves of polymer electrolytes prepared with different molar ratios of polyethylene oxide and cesium fluoride
[0038] Figure 4 Scanning electron micrographs of polymer electrolytes prepared with a molar ratio of polyethylene oxide to cesium fluoride of 10:1 (left) and a molar ratio of polyacrylonitrile to cesium fluoride of 5:1 (right)
[0039] Figure 5 Constant current charge-discharge cycle curve of the polymer electrolyte prepared with a molar ratio of polyethylene oxide to cesium fluoride of 3:1 DETAILED DESCRIPTION
[0040] The present invention is described in detail below with reference to the accompanying drawings and embodiments:
[0041] Example 1
[0042] 1) Polyethylene oxide macromolecules and cesium fluoride were weighed as raw materials in a molar ratio of 3:1. First, 1.0 g of the polymer macromolecule was added to a beaker containing 25 ml of acetonitrile solvent and stirred until completely dissolved. Then, cesium fluoride was added to the above solution and stirred for 24 hours to obtain a uniform polymer solution.
[0043] 2) Step 2: The polymer solution obtained in step 1 was injected into a customized polytetrafluoroethylene mold, allowed to stand at room temperature for 12 hours, and then transferred to a vacuum oven and heated at 60° C. for 12 hours until the organic solvent was completely evaporated to obtain a flexible polymer electrolyte.
[0044] The flexible polymer electrolyte prepared in Example 1 was assembled in a CR2032 commercial button cell in the manner of stainless steel sheet|polymer electrolyte|stainless steel sheet, and then transferred to a Shanghai Chenhua CHI660 electrochemical workstation for electrochemical impedance spectroscopy testing. The test conditions were: amplitude 5 mV, test frequency range 0.1 Hz-10 5 Hz, test temperature 30-70℃. Before each test, the sample was kept at the corresponding temperature for 1h and the test was repeated three times. Figure 1 As shown, the obtained electrochemical impedance spectrum consists of a concave semicircle (non-ideal state) and a slanted straight line. The semicircle represents the charge transfer resistance of the polymer electrolyte, and the straight line represents the diffusion resistance of F ions in the electrolyte. The charge transfer resistance of the prepared polymer electrolyte is less than 150 ohms, and decreases with increasing temperature. The ionic conductivity of the polymer electrolyte is calculated according to the formula σ=L / (RxS). Where L is the thickness of the membrane; S is its area; and R is its impedance. As shown in the attached figure Figure 2 As shown in Figure 2, the prepared polymer electrolyte exhibits a high fluoride ion conductivity of 1.2 mS cm at 70 °C. -1 .
[0045] The flexible polymer electrolyte prepared in Example 1 was assembled in a CR2032 commercial button cell in the manner of stainless steel sheet|polymer electrolyte|Pb foil, and then transferred to a Shanghai Chenhua CHI660 electrochemical workstation to test the electrochemical window. Figure 3 As shown, the prepared polymer electrolyte is stable between -1.8V and +1.2V.
[0046] The flexible polymer electrolyte material prepared in Example 1 was assembled into a fluoride ion battery with a copper fluoride / mesoporous carbon composite material positive electrode and a lead foil negative electrode in a CR2032 commercial button cell. Constant current charging and discharging was performed on a blue electric tester. Figure 5 As shown, as a positive electrode material for fluoride ion batteries at 2 mA g -1 At a current density of 589 mA hg -1 The specific capacity can be cycled 250 times.
[0047] Example 2
[0048] The operation method is the same as that of Example 1, except that the molar ratio of polyethylene oxide macromolecule to cesium fluoride is 10:1. Figure 4 As shown in the figure, the prepared flexible polymer electrolyte is assembled from spherulites with a diameter of about 650 μm, and there are a small amount of gaps between the spherulites; as shown in the attached Figure 2 As shown in Figure 2, the flexible polymer electrolyte exhibits a high fluoride ion conductivity of 0.035 mS cm at 70 °C. -1 ; as attached Figure 3As shown, the prepared polymer electrolyte is stable between -3V and +3V.
[0049] Example 3
[0050] The operation method is the same as that of Example 1, except that the molar ratio of polyethylene oxide macromolecule to cesium fluoride is 16:1. Figure 2 As shown in Figure 2, the flexible polymer electrolyte exhibits a high fluoride ion conductivity of 0.069 mS cm at 70 °C. -1 ; as attached Figure 3 As shown, the prepared polymer electrolyte is stable between -3V and +3V.
[0051] Example 4
[0052] 1) Weigh polyacrylonitrile macromolecule and cesium fluoride as raw materials at a molar ratio of 5:1. First, add 0.8 g of the polymer macromolecule into a beaker containing 20 ml of acetonitrile solvent and stir until it is completely dissolved. Then, add cesium fluoride to the above solution and continue stirring for 24 hours to obtain a uniform polymer solution.
[0053] 2) Step 2: The polymer solution obtained in step 1 is injected into a customized polytetrafluoroethylene mold, left to stand at room temperature for 24 hours, then transferred to a vacuum oven, and heated at 65°C for 20 hours until the organic solvent is completely evaporated to obtain a flexible polymer electrolyte.
[0054] As attached Figure 4 As shown, the surface of the prepared flexible polymer electrolyte is smooth and no obvious grain boundaries are observed, indicating that cesium fluoride salt reduces the crystallinity of PEO and eliminates the grain boundaries inside the polymer matrix by disrupting the regular arrangement of polymer molecular chains.
[0055] The preferred embodiments of the present invention have been specifically described above, but the present invention is not limited to the embodiments. Those skilled in the art may make various equivalent modifications or substitutions without violating the spirit of the present invention. These equivalent modifications or substitutions are all included in the scope defined by the claims of this application.
Claims
1. A method for preparing a flexible polymer electrolyte with fast fluoride ion conduction, characterized in that: The preparation method is prepared according to the following steps: Step 1: Weigh polymer macromolecules and inorganic fluoride salt as raw materials in a certain molar ratio, first add a certain mass of polymer macromolecules into a beaker containing a certain volume of organic solvent and stir until completely dissolved, then add inorganic fluoride salt to the above solution and continue stirring for a certain period of time to obtain a uniform polymer solution; Step 2: Inject the polymer solution obtained in step 1 into a customized polytetrafluoroethylene mold, let it stand at room temperature for a period of time, then transfer it to a vacuum oven, and heat it at a set temperature for a period of time until the organic solvent is completely evaporated to obtain a flexible polymer electrolyte.
2. The preparation method according to claim 1, characterized in that: The molar ratio of the polymer macromolecule and the inorganic fluoride salt selected in step 1 is 18:1, 16:1, 12:1, 10:1, 8:1, 5:1, 3:1, 2:1 or 1:1, but is not limited to the listed values, and other values not listed within the numerical range are also applicable; Preferably, the polymer macromolecule selected in step 1 includes any one of polyvinylidene fluoride, polyacrylonitrile, polyethylene oxide, polymethyl methacrylate, polyethylene imine, polypropylene, carboxymethyl cellulose, alginate, pectinate, carrageenan, or a combination of at least two thereof, preferably polyethylene oxide; Preferably, the inorganic fluoride salt selected in step 1 includes any one of sodium fluoride, potassium fluoride, cesium fluoride, and rubidium fluoride, or a combination of at least two thereof, preferably cesium fluoride; Preferably, the mass of the polymer macromolecule selected in step 1 is 0.5-1.0 g, which can be 0.5 g, 0.6 g, 0.7 g, 0.8 g, 0.9 g or 1.0 g, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
3. The preparation method according to claim 1-2, characterized in that: Preferably, the organic solvent selected in step 1 includes any one of methanol, ethanol, acetone, chloroform, ether, acetonitrile, dimethyl sulfoxide, tetrahydrofuran, N,N-dimethylformamide or a combination of at least two thereof, preferably acetonitrile solvent; Preferably, the volume of the organic solvent selected in step 1 is 15-40 ml, which can be 15 ml, 20 ml, 25 ml, 30 ml, 35 ml or 40 ml, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
4. The preparation method according to any one of claims 1 to 3, characterized in that Preferably, the stirring time selected in step one is 12-48h, for example, it can be 12h, 16h, 20h, 24h, 28h, 32h, 36h, 40h, 44h or 48h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The standing time selected in step 2 includes 6-24 hours, for example, 6 hours, 12 hours, 18 hours or 24 hours, but is not limited to the listed values, and other values not listed within the numerical range are also applicable; Preferably, the heating temperature selected in step 2 includes 60-80°C, for example, 60°C, 65°C, 70°C, 75°C or 80°C, but is not limited to the listed values, and other values not listed in the numerical range are also applicable; Preferably, the heating time selected in step 2 includes 12-24 hours, for example, it can be 12 hours, 14 hours, 16 hours, 18 hours, 20 hours or 24 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
6. The preparation method according to any one of claims 1 to 5, characterized in that: The preparation method comprises: Step 1: Weigh polymer macromolecules and inorganic fluoride salt as raw materials at a molar ratio of 18:1-1:1, first add 0.5-1.0g of polymer macromolecules into a beaker containing 15-40ml of organic solvent and stir until completely dissolved, then add inorganic fluoride salt to the above solution and continue stirring for 12-48h to obtain a uniform polymer solution; Step 2: Inject the polymer solution obtained in step 1 into a customized polytetrafluoroethylene mold, let it stand at room temperature for 6-24 hours, then transfer it to a vacuum oven, and heat it at 60-80°C for 12-24 hours until the organic solvent is completely evaporated to obtain a flexible polymer electrolyte.
7. A flexible polymer electrolyte, characterized in that: The flexible polymer electrolyte is obtained by the preparation method according to any one of claims 1 to 6; Preferably, the flexible polymer electrolyte has high flexibility, strong film-forming ability, low interface resistance with the electrode, and high ion conductivity.
8. Use of the flexible polymer electrolyte according to claim 6 or 7, characterized in that: The flexible polymer electrolyte is assembled with a metal fluoride / carbon composite material positive electrode and a lead foil negative electrode for use in a fluoride ion battery; Preferably, the method for using the flexible polymer electrolyte is to sequentially place the positive electrode material of the fluoride ion battery, the flexible polymer electrolyte, and the negative electrode material in a CR2032 commercial button battery for assembly testing.